Enhanced Removal of Paracetamol Using Biogenic Manganese Oxides Produced by Pseudomonas putida B-14878 and Process Optimization by RSM - Tepe, Ozlem; Comert, Semih (Springer Int Publ Ag, 2019)
Over the last few decades, many classes of micropollutants have been detected in aquatic environments worldwide and paracetamol is one of the micropollutant agents detected in the aquatic environment. New treatment methods based on biologically produced metal and metal oxides have been developed for micropollutant removal. Biogenic manganese oxides are also one of the most important biogenic metal oxide species. In this study, biogenic manganese oxides produced by manganese-adapted Pseudomonas putida NRRL B-14878 were used for removing paracetamol. A complete removal of paracetamol could be achieved within 216 h at pH 7, biogenic manganese oxide amount of 5 g/L, and paracetamol concentration of 2 mg/L. Response surface methodology (RSM) was applied to determine interaction between solution pH, paracetamol concentration, and biogenic manganese oxide amount being individual variables and to optimize operating conditions. According to results of variance analysis (ANOVA), the second-order polynomial model was statistically significant and coefficient of determination value was high. The optimal conditions were obtained as the solution pH of 6.81, the paracetamol concentration of 9.82 mg/L, and the biogenic manganese oxide amount of 6.36 g/L. Transformation products including the dimers, higher-degree oligomers, 3-hydroxyacetaminophen, 4-aminophenol, 4-methoxyphenol, 1,4-dimethoxybenzene, and butenedioic acid were identified by LC-MS/MS. The results of this work indicate that biogenic manganese oxide is an effective material for removing micropollutants.
Keywords: Biogenic manganese oxides; Pharmaceutical; Paracetamol; Pseudomonas putida NRRL B-14878; Removal; Response surface methodology